Applying the Theory Of Planned Behavior (TPB) to explain the adoption of green building / Nurul Hidayana Mohd Noor, Noor Syazwani Azizan and Nur Syairah Abu Hasan - Mohd Noor, Nurul Hidayana; Azizan, Noor Syazwani; Abu Hasan, Nur Syairah (Universiti Teknologi MARA, Perak, 2023)
Green building is defined as efficiently using water, materials, and energy and the impact on the environment and human health. Therefore, this study aims at identifying the factors affecting the implementation of green buildings in Malaysia. The method used in this study is quantitative and uses a "positivism" approach. The questionnaire was prepared using the five-point Likert scale. The questionnaire was sent to 384 respondents in Malaysia, and 330 valid responses were received in return. This research was analyzed using IBM SPSS Version 23.0. The results of the Pearson Correlation test have shown that there is a significant relationship between five selected determinants, namely cost (r =0.717, p = 0.000), attitude (r =0.765, p = 0.000), information, knowledge, and awareness (r =0.751, p = 0.000), management and government (r =0.823, p = 0.000), and technology and training (r =0.773, p = 0.000) towards intention in adopting green building technology. Next, the most dominant factor was management and government (β = 0.487, p= 0.000). This study is expected to motivate the use of green buildings based on selected determinants. Discussions were also made concerning aspects of the implications and recommendations of the study.